1993
DOI: 10.7164/antibiotics.46.465
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mode of antifungal action of pradimicin antibiotics. III. Spectrophotometric sequence analysis of the ternary complex formation of BMY-28864 with D-mannopyranoside and calcium.

Abstract: Sequence of reactions in the process of ternary complex formation of BMY-28864 with D-mannopyranosideand calcium was spectrophotometrically determined nnder more strict analytical conditions using metal-free preparations of sugars and the pradimicin derivative at a bandpass slit width of 1 nm. In the first phase of ternary complex formation, BMY-28864stereospecifically recognized and bound to D-mannopyranoside in the absence of calcium, which was revealed by a visible absorption maximumshift of ca. 8 nm. Subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 28 publications
3
31
0
Order By: Relevance
“…Since no N-glycan deletions have ever been observed in gp41 of PRM-A-resistant (8) and PRM-Sresistant (this study) virus strains, this binding to gp41 may most likely not be directly related to the eventual antiviral activity of the pradimicins. The pradimicins have been suggested to be physiologically active as a (dimeric) complex with Ca 2ϩ (17,29,30). Experimental evidence has indeed been provided that in the presence of PRM-A, (␣-1,2)mannose oligomers, and Ca 2ϩ , a ternary complex is formed that consists of one Ca 2ϩ ion, two pradimicin-A molecules and four (␣-1,2)mannose oligomers (17,29,30).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since no N-glycan deletions have ever been observed in gp41 of PRM-A-resistant (8) and PRM-Sresistant (this study) virus strains, this binding to gp41 may most likely not be directly related to the eventual antiviral activity of the pradimicins. The pradimicins have been suggested to be physiologically active as a (dimeric) complex with Ca 2ϩ (17,29,30). Experimental evidence has indeed been provided that in the presence of PRM-A, (␣-1,2)mannose oligomers, and Ca 2ϩ , a ternary complex is formed that consists of one Ca 2ϩ ion, two pradimicin-A molecules and four (␣-1,2)mannose oligomers (17,29,30).…”
Section: Discussionmentioning
confidence: 97%
“…The pradimicins have been suggested to be physiologically active as a (dimeric) complex with Ca 2ϩ (17,29,30). Experimental evidence has indeed been provided that in the presence of PRM-A, (␣-1,2)mannose oligomers, and Ca 2ϩ , a ternary complex is formed that consists of one Ca 2ϩ ion, two pradimicin-A molecules and four (␣-1,2)mannose oligomers (17,29,30). In the absence of Ca 2ϩ , PRM-A and PRM-S are unable to bind to HIV-1 gp120 in SPR experiments.…”
Section: Discussionmentioning
confidence: 99%
“…10 These sugars have an arrangement similar to the 2-, 3-, and 4-hydroxyl groups of D-Man (Fig. 3), and are thus expected to bind to PRMs in the same manner as D-Man.…”
Section: Introductionmentioning
confidence: 98%
“…1), an artificial PRM derivative with improved water solubility, 8 revealed that PRMs and Ca 2+ ion form the binary [PRM/Ca 2+ ] complexes, which bind D-Man but not L-mannose, 2-, 3-, and 4-epimers of D-Man (D-glucose, D-altrose, and D-talose, respectively), D-mannosamine, and N-acetyl-D-mannosamine. 9,10 This sugar-binding profile led to the assumption that PRMs recognize the 2-, 3-, and 4-hydroxyl groups of D-Man.…”
Section: Introductionmentioning
confidence: 99%
“…It specifically binds to the terminal D-mannose pyranosides of ␣(1,2)-mannose oligomers. It requires the presence of Ca 2ϩ , which is thought to bind two PRM-A molecules through the free carboxylic acid group present on each molecule (Ueki et al, 1993).…”
mentioning
confidence: 99%